Effi cacy of some natural compounds as antifungal agents - Vengurlekar, Sudha; Sharma, Rajesh; Trivedi, Piyush (Pharmacognosy Reviews, 2012)
Natural sources have been important for the development of new active molecules for many years. Various small molecules with unique chemical skeleton and potent bioactivities were discovered through various sources like plants, marine products, and microorganisms, etc., which are considered as very important part of the nature. A number of potent antifungals have been originated from various natural sources. This account describes structure and activities of selected agents isolated from various natural sources.
Keywords: Antifungals; biological activities; chemical structure; natural sources